IMPACT OF SEED TREATMENT CHEMICALS ON SEED STORABILITY IN PIGEONPEA (CAJANUS CAJAN (L.) MILLSP.) - PATIL, SHIVAGOUDA; PRASAD S, RAJENDRA; BADIGER, BHARAMARAJ; HIPPARAGI, YEGAPPA; MARUTHI K; SHANKRAYYA (The Bioscan, 2014)
The storage experiment on influence of seed treatment chemicals on seed quality in pigeonpea Cv. BRG-1. From the present investigation it could be concluded that thiram @ 3 gm/kg of seed + spinosad @ 0.04 ml/kg of seed which were stored in superbag recorded significantly higher germination (83.50%), seedling length (30.43 cm), seedling dry weight (28.90mg), seedling vigour index-I (2555) and II (2427), seed moisture is lowest recorded 8.45% at the end of sixth months of storage period compared to control.